Domestic and international impacts of rice export restrictions: The recent case of indian non-basmati rice - Valera, Harold Glenn A.; Mishra, Ashok K.; Pede, Valerien O.; Yamano, Takashi; Dawe, David (Elsevier, 2024)
This study examines the impact of India's export restrictions on domestic retail rice prices using a dynamic panel GARCH model. The findings suggest that export restrictions are not a sufficient condition to lower domestic prices. Export restrictions are associated with lower retail price volatility in the East Zone. Moreover, the international price transmission to a sample of Asian and African economies shows that all countries are vulnerable, but the degree and kinds of vulnerability differ. Rice exporters appear to be the most susceptible as domestic prices increase in these countries. Rice importers are also vulnerable because of price increases, but the increases are less than in countries where the private sector decides on import quantities.